Pengaruh Fly Ash pada Stabilisasi Lempung Ekspansive Terhadap Nilai Tegangan Geser dan CBR - Elsy E. Hangge; Remigildus Cornelis; Antonius Y. Dom (JURNAL FORUM TEKNIK SIPIL (J-ForTekS), 2022)
Expansive clay soils are categorized as poor as subgrades because of their low capacity for bearing soil. Therefore, it needed to stabilize with added lime and fly ash materials. This study aimed to determine the effect of adding lime and fly ash on the bearing capacity of expansive clay in the form of shear stress and CBR values. The research method used is observation, namely testing of physical and mechanical properties in the laboratory. The tests were carried out on the original soil, and soil was stabilized using 5% lime, and the fly ash content was 10%, 20%, 30%, 40%, and 50%. The biggest change in the value of the CBR test occurred in the CBR value that was not submerged after seven days of curing on a variation of a mixture of 5% lime (fixed) and 50% fly ash, which was 11.74% of the original soil CBR value of 1.39%. The largest increase in soil bearing capacity (qu) and undrained soil cohesion (cu) was obtained in the composition of the original soil mixture, 5% lime and 50% fly ash, namely 0.368 kg/cm2 and 0.184 kg/cm2. The results showed that the stabilization of expansive clay using lime and fly ash increased the bearing capacity of the soil.